Peran Guru Pendidikan Agama dalam Mengembangkan Kreativitas Siswa Kelas V Sekolah Dasar Santo Thomas 4 Medan - Simbolon, Erikson; Nainggolan, Lioni Ogilvi (Universitas Batanghari Jambi, 2024)
Students' ability to understand PAK material partly depends on the teacher. Students must be able to follow the learning process in class clearly in order to understand the material in PAK. The reality that occurs in the field is that many students are not creative in addressing problems in life in relation to life in accordance with the teachings of their faith. Because students lack creativity, it causes many students to disrespect friends, disrespect teachers, parents and also people in the surrounding environment. The purpose of this research is to find out the role of teachers in developing students' creativity in PAK subjects at St. Thomas 4 Medan Elementary School. PAK teachers have an important role in guiding students in contrast to the role of teachers in general. Students at SD Santo Thomas 4 Medan experienced an increase in creativity, this can be seen from the achievement of creativity indicators, namely having a high drive, having high involvement, having great curiosity, daring to express opinions and beliefs. From the results of research or research see that PAK teachers at SD Santo Thomas 4 Medan are very instrumental in developing creativity in the learning process. 2. Student creativity in PAK learning has increased. This can be seen from the fulfillment of creativity indicators.